Omnichannel Fashion Retail in Indonesia: How it affects Marketing Performance? - Nizar Alam Hamdani; Arum Mutmainah; Galih Abdul Fatah Maulani; Sukma Nugraha; Intan Permana (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: Mobile commerce is an appropriate omnichannel practice adoption for fashion retail. Omnichannel in the retail industry is currently becoming an innovation strategy to increase consumer interaction by integrating various sales channel services. Consumers' channel-switching behavior remains as one of the challenges in the retail industry. To deal with these challenges, providing multiple points of contact to interact with consumers that gain competitive advantage and improve marketing performance is required.Methodology: This study is a causal research with a 95% confidence interval in collecting and constructing the data structure to evaluate the cause-and-effect relationship of the variables. The primary data was obtained through a survey of 91 retail fashion consumers in Indonesia. Subsequently, the data was analyzed using structural equation modeling.Finding: Compared to the previous studies, the results of this study indicated that novelty, hedonic, and utilitarian motivations influence brand love through omnichannel customer experience. To improve brand love, companies need to improve customer experience.Conclusion: Based on the findings, the researchers felt one of the biggest flaws in the study was only collecting data on consumers of international clothing products whose physical stores have only been operating in Indonesia